Hygienic evaluation of modern technologies for handling with solid domestic waste and prospects for their implementation in Ukraine (Environment & Health, 2017)
Objective: We presented a sanitary–and-hygienic assessment of modern methods for recycling and disposal of solid domestic waste (SDW) and prospects of their implementation in Ukraine.Materials and methods: The unutilized residue of SDW after industrial sorting was the material of the study. Investigations of the influence of waste sorting on the composition and properties of the unutilized residue of solid waste were carried out by us under field condition at the garbage sorting station of JSC "Greenco-Center", Kyiv. The study was performed according to the standard procedures. Heavy metals were determined by the atomic absorption method with the help of spectrophotometer of CAS-120.1type. The biological activity of the waste was determined by the index of dehydrogenase activity. The dehydrogenase activity of the waste was determined by the modified methodology in accordance with the Patent of Ukraine No. 22364. Influence of biological preparations on the acceleration of the decomposition of organic waste was evaluated by the dynamics of the reduction of SDW weight and the release of filtrate in time.Results: There is an analysis of modern methods for recycling and disposal of SDW in the work. It is shown that unutilized part of SDW after sorting is safer for disposal. The content of heavy metals decreases in the content of unutilized SDW after sorting and, vice versa, a certain increase of microelements’ content is registered in it. After sorting, in the unutilized part of SDW a content of heavy metals (lead, cadmium, nickel, cobalt) doesn’t exceed their clarkes and MAC in soil in contrast to native SDW. The methods for the optimization of handling with the unutilized part of SDW after sorting are proposed. Compaction of the mixture (10 parts of waste to 1 part of ash) up to 1 kg / cm3 causes a minimization of biological decomposition of the organic substances. When enzyme (oxyzine) and microbial preparations (EM-1) are used for the recycling of SDW after sorting, the decomposition’s depth of organic substances is greater by 1.5 (oxyzine) - 1.7 (EM-1) fold than under natural destruction.
Keywords: solid domestic waste (SDW); sorting of waste; unutilized residue of solid domestic waste after sorting; compaction; biopreparations